In-depth structural characterization of Kadcyla® (ado-trastuzumab emtansine) and its biosimilar candidate. Issue 7 (2nd October 2016) - Chen, Liuxi; Wang, Lan; Shion, Henry; Yu, Chuanfei; Yu, Ying Qing; Zhu, Lei; Li, Meng; Chen, Weibin; Gao, Kai
ASBTRACT: The biopharmaceutical industry has become increasingly focused on developing biosimilars as less expensive therapeutic products. As a consequence, the regulatory approval of 2 antibody-drug conjugates (ADCs), Kadcyla® and Adcetris® has led to the development of biosimilar versions by companies located worldwide. Because of the increased complexity of ADC samples that results from the heterogeneity of conjugation, it is imperative that close attention be paid to the critical quality attributes (CQAs) that stem from the conjugation process during ADC biosimilar development process. A combination of physicochemical, immunological, and biological methods are warranted in order to demonstrate the identity, purity, concentration, and activity (potency or strength) of ADC samples. As described here, we performed extensive characterization of a lysine conjugated ADC, ado-trastuzumab emtansine, and compared its CQAs between the reference product (Kadcyla®) and a candidate biosimilar. Primary amino acid sequences, drug-to-antibody ratios (DARs), conjugation sites and site occupancy data were acquired and compared by LC/MS methods. Furthermore, thermal stability, free drug content, and impurities were analyzed to further determine the comparability of the 2 ADCs. Finally, biological activities were compared between Kadcyla® and biosimilar ADCs using a cytotoxic activity assay and a HER2 binding assay. The in-depth characterization helps to establish product CQAs, and is vital for ADC biosimilars development to ensure their comparability with the reference product, as well as product safety.